Havana Tradition Platform Pipe Production and Disposition: Implications for Interpreting Regional Variation in Midwestern Hopewell Ceremonialism. Issue 4 (October 2021) - Farnsworth, Kenneth B.; Emerson, Thomas E.; Hughes, Randall E.
Abstract : This study documents the contexts of platform pipe creation, distribution, and disposition at Illinois Havana Hopewell Tradition (50 BC to AD 200–250) sites to identify regional variation in Hopewell ceremonialism and exchange. We observe that the large deposits of stone pipes buried during communal rituals in the Scioto Valley and the continued influence of the Hopewell Sphere of Interaction have skewed archaeological interpretation. Aside from the several large deposits, pipes are limited in the Scioto Tradition and seldom found in habitation areas. In Illinois, pipe fabrication debris commonly occurs in habitation areas along with numerous examples of pipe repair and maintenance. Local pipestones—often from northern Illinois Sterling deposits—predominate, and exotic imported pipestones are unusual. Pipes are rare inclusions with individual burials as indicators of status, spiritual prowess, achievement, or group membership. The high value placed on pipes as communal sacra in Ohio and their value in Illinois as items of personal influence parallels their common occurrence in Illinois and their unique context in Ohio Hopewell. This study of the contexts of pipe manufacture and deposition reinforces current discussions of such artifact assemblages as important in documenting local variations in political, social, and religious mortuary ceremonialism across the "Hopewellian sphere."